Charged pion production in p+C collisions at 158 GeV/c beam momentum: Discussion - Barr, G; Chvala, O; Fischer, H; Kreps, M; Makariev, M; Pattison, C; Rybicki, A; Varga, D; Wenig, S (2007)
The new data on pion production in p+C interactions from the NA49 experiment at the CERN SPS are used for a detailed study of hadronization in the collision of protons with light nuclei. The comparison to the extensive set of data from p+p collisions obtained with the same detector allows for the separation and extraction of the projectile and target contributions to the pion yield both in longitudinal and in transverse momentum. © 2007 Springer-Verlag.